2015
DOI: 10.1177/0883073815600863
|View full text |Cite
|
Sign up to set email alerts
|

Remote Assessment of Cognitive Function in Juvenile Neuronal Ceroid Lipofuscinosis (Batten disease)

Abstract: Remote technology provides an opportunity to extend the reach of clinical care and research for pediatric rare disease. This pilot study evaluated the feasibility and reliability of neuropsychological evaluation, using remote audiovisual technology, in the assessment of children with juvenile Batten disease. Three children with Batten disease and one healthy sibling completed a standardized cognitive assessment. Results indicated high agreement between an in-person and a remote evaluator, when comparing the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 32 publications
0
38
0
Order By: Relevance
“…Previous studies used very small test batteries and often intentionally selected subtests that were predominantly verbal in nature (to be amenable to their technology/methodology). 21,22 The current study did not exclude nonverbal subtests even including a visuo-constructional task (block design); made possible by using two document cameras (one for the child and one for the assessor) and split-screen mechanisms (one showing the psychologist and the other presenting the block design). Furthermore, when visual tasks were attempted via telehealth in previous studies, the presentation of test material required the examiner to hold up the visual stimulus in front of the webcam or under a document camera.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies used very small test batteries and often intentionally selected subtests that were predominantly verbal in nature (to be amenable to their technology/methodology). 21,22 The current study did not exclude nonverbal subtests even including a visuo-constructional task (block design); made possible by using two document cameras (one for the child and one for the assessor) and split-screen mechanisms (one showing the psychologist and the other presenting the block design). Furthermore, when visual tasks were attempted via telehealth in previous studies, the presentation of test material required the examiner to hold up the visual stimulus in front of the webcam or under a document camera.…”
Section: Discussionmentioning
confidence: 99%
“…Ragbeer et al (2015) conducted a feasibility pilot study involving three children with Batten disease and one healthy sibling (age range 10-16 years) on select subtests of the Wechsler Intelligence Scale for Children -Fourth Edition and the Wide Range Assessment of Memory and Learning -Second Edition. 21 Testing was undertaken in the same building in two separate rooms, with an assessor in one room and a graduate student sitting with the child in another. While the study clearly has limitations, such as exclusion of nonverbal subtests and small sample size, it nonetheless demonstrated initial feasibility as testing was well tolerated by children and the technology worked effectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remote assessments can reduce burdensome, costly travel for patients and families and increase patient access to research studies [13]. For researchers, remote assessment may facilitate data capture from a larger number of individuals and increase data quality by reducing the number of assessors, increasing measurement expertise, and providing a more controlled environment.…”
Section: Approaches For Assessing Cognition and Behaviormentioning
confidence: 99%
“…In general, studies have also found participants are accepting and comfortable with the use of technology in performing cognitive assessments (Hildebrand et al, 2004; Parikh et al, 2013). Fewer pediatric studies exist assessing reliability of remote cognitive testing but include assessments of children with Batten disease, learning disabilities, and psychosis (Hodge et al, 2019; Ragbeer et al, 2016; Stain et al, 2011). However, none of the remote testing sites in these pediatric studies were conducted in home settings but rather hotel rooms during disease based conferences or within a designated testing site with patients in one room and assessor in another.…”
Section: Introductionmentioning
confidence: 99%